Identification of Gastrointestinal Endoparasite in Bawean Deer (Axis kuhlii) and Spotted Deer (Axis axis) at Bratang Flora Park – Surabaya - Hartono Hartono; Endang Suprihati; Erma Safitri; Nunuk Dyah Retno Lastuti; Mufasirin Mufasirin; Kusnoto Kusnoto (Journal of Parasite Science (JoPS), 2019)
The purpose of this study is to identify the endoparasites of Spotted Bawean Deer (Axis kuhlii) and Deer (Axis axis ) at Surabaya Flora Park. The research was conducted in December 2018 - January 2019 used total 60 specimen of sample faeces, consist of 30 sample of bawean deers faeces and 30 sample of spoted deers faeces, the samples analyzed at the Department of Parasitology Veterinary, Faculty of Veterinary Medicine, Universitas Airlangga. The results of the study found positive endoparasites on examination, samples of Bawean deer faeces (Axis kuhlii) and Spotted deer faeces(Axis axis) in Baratang Flora Park Surabaya found that 26 positive samples from 60 samples were obtained. Positive endoparasitic samples are protozoa at the stage of oocyst, namely Eimeria sp. 6 (10%) samples, worm eggs from the Nematoda class, Haemonchus sp. 20 (33.33%) and whereas endoparasites from other stages and classes were not found. The results of the analysis used Chi-Square test and showed no significantly differences degree of gastrointestinal endoparasite infection of Bawean deer (Axis kuhlii) and Spotted deer (Axis axis) (p>0.05).